(untitled) (International relations and international law Journal, 2018)
The article is devoted to the contemporary conditions of development of foreign trade activity andworld economic relations, whichconfirms the need to establish the innovative system of specialists training, based on practice and competence approaches. The aim of the innovative educational programs of universities is to improve communication of the future obtaining business (professional) qualifications. An important component of the training of students of a specialty «World Economy» is used in the process of training professional oriented technologies, the use of assignments using the method of simulating the professional activity, the analysis of work situations. This stimulates cognitive motivation in the field of professional activity, which leads to conscious acceptance of students personal qualities that define the success of future professional activity and increase their level of formedness. Relevant to the future speciality is largely determined by the nature of academic work, which is believed by many researchers should be modeled in a certain way to design the future professional activity. Organization of educational process is to make the transition from student to specialist positions, followed by transformation into a professional training activities. Key words: innovative education, innovative educational programs, social partnership model, practice-oriented approach, the competence approach.